Cuneiform Descriptions of Transient Phenomena. Issue Volume 14:Issue A30(2018) (August 2018) - Hunger, H.
Abstract: Sources from Ancient Mesopotamia contain mention of transient astronomical phenomena in two contexts: in records of observations, many of which can be dated, and in collections of omens, which use the appearance of such phenomena to predict future events. These omens consider quite a range of phenomena, but only rarely can they be dated in a precise way. This paper describes how transient phenomena were handled in both kinds of context.